PENGARUH BHAGAWAD GITA BERGAMBAR DAN VISUAL LITERACY TERHADAP PEMAHAMAN AJARAN HINDU SISWA SMP DI PASRAMAN TIRTA BHUANA BEKASI - I Ketut Ulianta; Ketut Angga Irawan (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2019)
The purpose of this study is to identify whether the use of different learning instructional media, that is Bhagawad Gita in the form of picture book and Bhagawad Gita in the form of plain text book, for students with different level of visual literacy, will results in any differences in the students’ understanding of the Hinduism value. This study aims to find out the answer to the questions (1) whether there are differences in the understanding of Hinduism value of students who in the learning process use Bhagawad Gita in the form of picture book compared to those who use Bhagawad Gita plain text book; (2) whether there are differences in the understanding of Hinduism value of students with a high visual literacy level who in the learning process use Bhagawad Gita in the form of picture book compared to those who use Bhagawad Gita plain text book; and (3) whether there are differences in the understanding of Hinduism value of students with a low visual literacy level who in the learning process use Bhagawad Gita in the form of picture book compared to those who use Bhagawad Gita plain text boo. This study applies Quantitative Analysis with Quasi-Experimental Design. The population are IX grade students of Pasraman Tirta Bhuana Bekasi of Academic Year 2016-2017. Samples are taken from the population using random sampling technique with a drawing method. The sample size are 32 students devided into two groups. Different treatment on the learning instructional media is given to each group after visual literacy of all samples are measured. Validity and reliability of the instrument are tested using Product Moment Correlation Technique and Alpha Cronbach's respectively. Two Way Analysis of Variance (ANOVA) with Treatment by Level Design is applied for data analysis.The results of this study are (1) there are differences in the understanding of Hinduism value of students who in the learning process use Bhagawad Gita in the form of picture book compared to those who use Bhagawad Gita plain text book; (2) the average learning outcome of students who have a high visual literacy level and use Bhagawad Gita in the form of picture book is higher than those who use Bhagawad Gita plain text book; and (3) the average learning outcome of students who have a low visual literacy level and use Bhagawad Gita in the form of picture book is higher than those who use Bhagawad Gita plain text book.